RECIPES FOR BUILDING THE DUAL OF CONIC OPTIMIZATION PROBLEM - Chaerani, Diah (Journal of the Indonesian Mathematical Society, 2010)
Building the dual of the primal problem of Conic Optimization (CO) isa very important step to make the ¯nding optimal solution. In many cases a givenproblem does not have the simple structure of CO problem (i.e., minimizing a linearfunction over an intersection between a±ne space and convex cones) but there areseveral conic constraints and sometimes also equality constraints. In this paper wedeal with the question how to form the dual problem in such cases. We discuss theanswer by considering several conic constraints with or without equality constraints.The recipes for building the dual of such cases is formed in standard matrix forms,such that it can be used easily on the numerical experiment. Special attention isgiven to dual development of special classes of CO problems, i.e., conic quadraticand semide¯nite problems. In this paper, we also brie°y present some preliminariestheory on CO as an introduction to the main topic.DOI : http://dx.doi.org/10.22342/jims.16.1.28.9-23